CONTEXTUALIZING ISLAMIC LAW IN THE ERA OF DISRUPTION: THE STRATEGIC ROLE OF NAHDLATUL ULAMA IN NAVIGATING RELIGIOUS, POLITICAL, AND EDUCATIONAL CHALLENGES - Syarifah , Masykurotus; Jamal, Nur; Karim, Muhammad Mujib (LPPM IAI Nazhatut Thullab, 2025)
The era of disruption has triggered profound shifts in various dimensions of human life, notably in the spheres of religion, politics, and education. These transformations necessitate a dynamic reinterpretation and application of Islamic law to ensure its continued relevance and efficacy. Nahdlatul Ulama (NU), the largest Islamic organization in Indonesia, plays a pivotal role in contextualizing Islamic legal thought to respond to contemporary social dynamics. This study explores NU’s adaptive legal approaches in addressing the challenges posed by digital disruption and socio-political changes. These efforts have proven instrumental in addressing current issues related to religious life, cultural politics, and educational reform in an increasingly disrupted world.